Understanding Sustainable Development in Organizational Contexts from the Establishment of Ideal Types - Munck, Luciano; de Souza, Rafael Borim (Organizações & Sociedade, 2014)
This article was developed with the objective of proposing ideal types to the orientation of the sustainable development. This purpose is presented because the managerial rationalities of the organizations are influenced by the territories where they are. The knowledge of the social, cultural, environmental and economic specificities of these places becomes needed to a better sustainable development management. The proposition of the ideal types aims to contribute to the decisions which are made in the organizations with coherent informations to a sustainable development. The contextualization of the ideal types counted with the following references: specific contributions of Weber’s Sociology (WEBER, 1964, 1968), the Heuristic Models of Ramos (1983), the individuals’ levels of existence indicated by Graves (1970, 1974) and the organizations’ levels of representativeness studied by Beck and Cowan (1996). Through the relations between these references it was proposed three ideal types of sustainable development: the archaic model of sustainable development, the transition model of sustainable development and the actualizing model of sustainable development. These ideal types present consistent potential to help organizations in decisions about limits, possibilities and challenges of working with and for the sustainable development in a managerial context.